KAJIAN YURIDIS TERHADAP KEDUDUKAN DAN KEWENANGAN KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI REPUBLIK INDONESIA - AGUS RUBIANSYAH NIM. A1011171031 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Corruption is a destructive culture that will continue to take root if it is not eradicated properly. In Indonesia, corruption is a big enemy that has not been able to be resolved. It is proven by the low Corruption Perception Index that Indonesia in 2022 is ranked 5th in ASEAN. The Corruption Eradication Commission (KPK) in carrying out its duties and authorities based on the mandate of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission.The problems studied are: